The Proper Role of Government in Response to the Current COVID-19 Pandemic - Gentile, Caroline (Maine Policy Review, 2022)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2022 asked students to consider what the proper role of government should be in responding to the current coronavirus pandemic. This is the third-place essay.